Pengetahuan dan Sikap Ibu Terhadap Kepatuhan Antenatal Care Tahun 2018 - Rani Oktarina (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2018)
The World Health Organization (WHO) states that to achieve the SDGs (Sustainable Development Goals) data the target by 2030 can reduce maternal mortality to below 70 per 100,000 live births. The purpose of this study was to determine the relationship of adherence and maternal attitudes towards adherence to antenatal care at the Sukajadi Health Center in Prabumulih City in 2018. This study used an analytical survey using a cross-sectional approach. The population of this study was all mothers who performed antenatal care at the Sukajadi Health Center in Prabumulih City in 2018, totaling 46 people. The number of samples in this study was 46 respondents. In the univariate analysis it was found that 46 respondents found that respondents who were well- informed as many as 27 respondents (58.7%), respondents who were quite good knowledge as many as 16 respondents (34.8%) and respondents who were less knowledgeable as many as 3 respondents (6.5 %). In the univariate analysis, it was found that 46 respondents found that respondents with a very good attitude as many as 34 respondents (73.9%), respondents with a good attitude as much as 4 respondents (15.2%), respondents with a bad attitude as many as 4 respondents (8, 7%) and respondents with a not very good attitude as much as 1 respondent (2.2%). Bivariate analysis shows that the mother's knowledge has a significant relationship with the incidence of antenatal care (p-value 0,000) and the attitude of the mother has a significant relationship with the incidence of antenatal care (p-value 0,000). This study concludes that there is a relationship of adherence and maternal attitudes towards adherence to antenatal care at the Sukajadi Health Center in Prabumulih City in 2018.